Effects of a training program on stable vs unstable surfaces on postural stability. [Efectos de un programa de entrenamiento en superficies estables frente a superficies inestables en la estabilidad postural]. - Alberto Encarnación-Martínez; Gemma María Gea-García (Ramón Cantó Alcaraz, 2019)
The training surface can modulate the body's response to training stimuli. The purpose of the article was to determine the influence of two types of training programs on stable/unstable surfaces on postural stability. 20 physically active participants with no history of lower limb injuries were randomly assigned to 3 groups (Control, Unstable Training, Stable Training), and performed supervised training in 16 sessions. Dynamic postural stability and static stability were assessed and tests were performed at baseline after completion of the training and 1, 2 and 4 weeks after the training process. The stable surface training group improved dynamic stability between the pre-test and the two first retention tests performed (p = .037, d = .780; p = .011, d = .989). The unstable training group significantly improved its dynamic stability level between the post-test and the retention test (2). The improvements found after the training session for the unstable training group do not mean an increase in stability higher than that obtained by the stable surface training group. The dynamic postural stability test seems more appropriate than the static tests for analyzing small changes related to the training of postural stability in healthy young people.